PETROLOGY AND PETROGENESIS OF SIAH KOOH VOLCANIC ROCKS IN THE EASTERN ALBORZ - Arian, Mohammad Ali; Baratian, Mostafa; Yazdi, Abdollah (Geosaberes; Vol 11 (2020): Vol 11 (2020)DO - 10.26895/geosaberes.v11i0.980, 2020)
Siah Kooh area is northeast of Shahroud city and is located in eastern Alborz. The lithologic composition of the volcanic rocks in the area consists of andesite, basalt, trachyandesite and quartztrachite. Plagioclase, olivine, and augite phenocrysts as the main minerals and apatite and magnetite, sericite, chlorite and apacite minerals are sub-minerals of volcanic rocks that are located in the glass slabs. Quartz is also found in fine-grained rock pulp and sometimes in phenocrysts. The dominant texture in these rocks are porphyritic, amygdaloidal and microlithic. According to geochemical studies of basaltic magmatic volcanic rocks, calc-alkaline potassium is high and negative Nb anomaly, Ce / Pb ratio and enrichment of rocks of light rare earth elements (LRRE) and high LREE / HREE ratio indicate contamination. The crust is an indicator of the presence of the garnet phase in the mantle source. On the other hand, the similarity of their trace elements to Oceanic Basalts (OIB) is a clear evidence of their relevance to this environment. Early basaltic magma originated from a mantle with a garnet-lherzolite composition with a partial melting rate of 15–12%. FeOtotal values in basalts and other structural evidence indicate the formation of these rocks in the early stages of intra-continental rifting which can be attributed to the pressure drop caused by intra-continental tidal phases associated with deep faults during the orogenic phases. Alpine attributed to Eocene time.